ANALISIS EKSPERIMENTAL PERPINDAHAN PANAS PADA MENARA PENDINGIN TIPE PLAT DATAR BERTINGKAT - Aulia, Fikri; Ahmad Syuhada; Razali, Razali (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Cooling towers serve as an important tool in industrial settings to reduce heat in machines that use water and air as working media, this process involves hot water generated from the machine coming into direct contact with air resulting in a small portion of the water evaporating which then reduces its temperature. Although previous research has attempted to improve the performance of cooling towers, there is still considerable scope for further exploration in achieving optimal results. One way to improve it is to adjust and change the flow of distributing fluid media by adding the number of holes on the flat plate of the cooling tower. Based on this phenomenon, the researcher wants to examine the magnitude of the heat transfer impact on a multi-storey cooling tower using triangular perforated flat plates with varying numbers of holes. The overall height of the cooling tower is 2.4 meters, consisting of five flat plates arranged in stages with each flat plate dimension having a length of 0.7 meters and a width of 0.5 meters, having a plate area of 3.5 m² with a tilt angle of each plate arrangement on the cooling tower which is 15 °. The number of holes in a given flat plate is 45, 55, and 65 holes, while the inlet water temperature is set at 80°C, 85°C, and 90°C. The results of this study revealed that the number of holes 65 showed a greater heat transfer effect compared to the other variations. Consequently, the number of holes significantly affects the heat transfer coefficient, thus impacting the overall performance of the multistage cooling tower.